Analisis Perspektif Auditor Kementerian Keuangan atas Pengawasan Intern Jarak Jauh - Mira Eka Irianti; Tubagus Muhammad Yusuf Khudri (Politeknik Ganesha Medan, 2023)
The study aims to analyze the perspective of government auditors on the use of remote internal supervision. A qualitative method with a case study approach is used in this study to get an overview of the use of remote internal control in organizations based on the UTAUT2 theory of technology use. Interviews were conducted with several auditors from various levels of Itjen Kemenkeu. The study finds that that the PIJJ method will be used by Itjen Kemenkeu auditors in the future. To maintain and increase the use of PIJJ in the future, the Itjen Kemenkeu needs to consider several factors that support the use of PIJJ, namely expectations of effort, expectations of performance, facilitative conditions, social influence, hedonic motivation, and habits. Organizations can provide training according to competency needs in PIJJ; use technology that is easy to use and user-friendly; promote the advantages and benefits of PIJJ for auditor performance; establishing a reward system for PIJJ's performance; managing organizational policies and culture; and arrangement of assignment teams. The results of this study have implications for the Inspector General of the Ministry of Finance and other government internal auditor organizations. Organizations can anticipate actions that need to be taken to increase the use of PIJJ.